MEDICINAL PLANTS WITH ANTIFERTILITY POTENTIAL OF SINDANG KELINGI ILIR TRIBE - IVONI SUSANTI; FITRIA LESTARI (CV KULTURA DIGITAL MEDIA, 2024)
This study aims to identify plants that have potential as antifertility in the Sindang Kelingi Ilir tribe. The method used in this research is exploration with data collection techniques in the form of field observations and interviews with tribal chiefs, traditional birth attendants, and the people of Sindang Kelingi Ilir. The results of this exploration found 19 species that have antifertility potential, namely: bandotan, cepokak, kate mas leaves, guava, jotang, meniran, patikan kebo, putri malu, knob grass, sintrong, dragon scale spikes, broken bones, noni, bitter melon, star fruit, sawo, makasar fruit, mondokaki, and mulberry. It is concluded that there are still plants that have potential as antifertility, which have minimal side effects.